Janus kinase/signal transducer and activator of transcription pathways in spondyloarthritis. Issue 4 (July 2017) - Raychaudhuri, Smriti K.; Raychaudhuri, Siba P.
Abstract : Purpose of review: Cytokines are major drivers of autoimmunity, and biologic agents targeting cytokines have revolutionized the treatment of immune-mediated diseases. Janus kinase/signal transducer and activator of transcription (JAK-STAT) pathway represents a group of several intracellular molecules with a key role in signal pathways activated by growth factors and cytokines. These kinase proteins are associated with the signaling process of multiple key cytokines, which regulates various T-cell subpopulations and their effector cytokines. Development of novel drugs to inhibit this kinase cascade is an emerging field in clinical immunology. Thus, it is essential to have insights about the regulatory role of the JAK-STAT cytokine signaling in relation to autoimmune diseases and its applications in spondyloarthritis. Recent findings: JAK-STAT kinase signaling proteins have been extensively studied in rheumatoid arthritis. Initial observations suggest that JAK-STAT kinase signaling cascade regulates activation and proliferation of the IL17 + effector memory T cells and thus has a potential role in the pathogenesis of psoriasis, psoriatic arthritis and ankylosing spondylitis. Summary: Here, we provide an overview of the clinical rheumatologists about the significance of JAK-STAT signaling system in rheumatic diseases and introduce the potential application of JAK and STAT inhibitors in spondyloarthritis.